Socioeconomic inequality in the prevalence of anemia: decomposing analysis among Kurdish people - Yousef Moradi; Asra Moradkhani; Azad Shokri; Pardis Mohammadzadeh; Mobin Azami; Ghobad Moradi; Nasrin Moghimi; Amjad Mohamadi Bolbanabad; Bakhtiar Piroozi; Farhad Moradpour (BMC Public Health)
Abstract Introduction Anemia is a prevalent public health issue affecting millions worldwide, particularly among vulnerable populations. This study examines anemia prevalence among Iran's Kurdish population, revealing socioeconomic inequality and emphasizing the need for targeted interventions. Materials & methods A cross-sectional analysis was conducted in 2019 using baseline data from the Dehgolan Prospective Cohort Study, involving 3,869 adults aged 35–70. Anemia was defined according to WHO guidelines, and socioeconomic status was assessed through household asset indices and educational attainment. Logistic regression and concentration index methods were employed to analyze the data. Results The prevalence of anemia was found to be 4.4%, with a higher rate in females (6.1%) compared to males (2.2%). Significant disparities were observed based on education and wealth, with illiterate individuals showing a prevalence of 5.5%. The analysis revealed that education and gender were the most influential factors contributing to socioeconomic inequality in anemia prevalence. Conclusion The study highlights the critical role of socioeconomic factors in the prevalence of anemia among the Kurdish population. Addressing these inequalities is essential for improving health outcomes and developing effective public health strategies.